Indicadores de desempenho: um modelo para avaliação em hotel - Moysés, Gerson Luis Russo; Zilber, Moisés Ari (Revista Gestão da Produção Operações e Sistemas, 2006)
This paper is about the identification of the trends of some hotel indicators, according to a model proposed byZilber and Fischmann. The theoretical fundamentation is based on authors such as Harland (1996), Castelli(2003), Vallen and Vallen (2003) and Walker (1999), regarding ‘hotelling and its value chain’; Whittington(2002) and Abell (1995), regarding ‘strategic planning’; Kaplan e Norton (1997) and Young (2003) regarding‘performance indicators’ and Pring (1999) and Zilber e Fischmann (2002 e 2001) regarding ‘moving average’.An exploratory research was carried out in a hotel in the countryside of the state of São Paulo, Brazil. The datacollection was performed by means of a documented analysis bewteen 2002 and 2004 and, for the handling ofthe data, the ‘arithmetic moving average’ was used. The results evidenced that the model is able to demonstratethe company’s performance trend and to subsidize the follow-up and the redefinition of the strategic planningprocess of the organization.Keywords: Indicators; Performance; Hotel.